Serious Games for Mental Health: Are They Accessible, Feasible, and Effective? A Systematic Review and Meta-analysis - Lau, Ho Ming; Smit, Johannes H.; Fleming, Theresa M.; Riper, Heleen (Frontiers in Psychiatry, 2017)
The development and use of serious games for mental health disorders are on the rise. Yet, little is known about the impact of these games on clinical mental health symptoms. We conducted a systematic review and meta-analysis of randomized controlled trials that evaluated the effectiveness of serious games on symptoms of mental disorder. Method: We conducted a systematic search in the Pubmed, PsycINFO and Embase databases, using mental health and serious games related keywords. Ten studies met the inclusion criteria and were included in the review, nine were included in the meta-analysis. Results: All of the serious games were provided via personal computer, mostly on CD-ROM without the need for an internet connection. The studies targeted age groups ranging from 7 to 80 years old. The serious games focussed on symptoms of depression (n = 2), post-traumatic stress disorder (n = 2), autism spectrum disorder (n = 2), attention deficit hyperactivity disorder (n = 1), cognitive functioning (n = 2) and alcohol use disorder (n = 1). The studies used goal-oriented (n = 4) and cognitive training games (n = 6). A total of 674 participants were included in the meta-analysis (380 in experimental and 294 in control groups). A meta-analysis of nine studies comprising ten comparisons, using a random effects model, showed a moderate effect on improvement of symptoms (g = 0.55 [95% CI 0.28 to 0.83]; P < 0.001), favoring serious games over no intervention controls. Discussion/Conclusion: Though the number of studies in the meta-analysis was small, these findings suggest that serious gaming interventions may be effective for reducing disorder related symptoms. More studies are needed in order to attain deeper knowledge of the efficacy for specific mental disorders and the longer term effects of this new type of treatment for mental disorders.